Comparison of genomic diversity and structure of sable antelope (Hippotragus niger) in zoos, conservation centers, and private ranches in North America. (27th April 2020) - Gooley, Rebecca M.; Tamazian, Gaik; Castañeda‐Rico, Susette; Murphy, Katherine R.; Dobrynin, Pavel; Ferrie, Gina M.; Haefele, Holly; Maldonado, Jesús E.; Wildt, David E.; Pukazhenthi, Budhan S.; Edwards, Cody W.; Koepfli, Klaus‐Peter
Abstract: As we enter the sixth mass extinction, many species that are no longer self‐sustaining in their natural habitat will require ex situ management. Zoos have finite resources for ex situ management, and there is a need for holistic conservation programs between the public and private sector. Ex situ populations of sable antelope, Hippotragus niger, have existed in zoos and privately owned ranches in North America since the 1910s. Unknown founder representation and relatedness has made the genetic management of this species challenging within zoos, while populations on privately owned ranches are managed independently and retain minimal‐to‐no pedigree history. Consequences of such challenges include an increased risk of inbreeding and a loss of genetic diversity. Here, we developed and applied a customized targeted sequence capture panel based on 5, 000 genomewide single‐nucleotide polymorphisms to investigate the genomic diversity present in these uniquely managed populations. We genotyped 111 sable antelope: 23 from zoos, 43 from a single conservation center, and 45 from ranches. We found significantly higher genetic diversity and significantly lower inbreeding in herds housed in zoos and conservation centers, when compared to those in privately owned ranches, likely due to genetic‐based breeding recommendations implemented in the former populations. Genetic clustering was strong among all three populations, possibly as a result of genetic drift. We propose that the North American ex situ population of sable antelope would benefit from a metapopulation management system, to halt genetic drift, reduce the occurrence of inbreeding, and enable sustainable population sizes to be managed ex situ.